Estrategias lúdicas para estimular el lenguaje en los niños y niñas de 5 a 6 años de la Unidad Educativa “Verbo Divino” cantón Guaranda provincia Bolívar periodo 2023 - Aguaguiña Cabrera, Rosa Maribel (2023)
The research project on Ludic Strategies to stimulate language in children from 5 to 6 years of age of the "Verbo Divino" Educational Unit Guaranda Canton Bolívar Province Period 2023, addresses various topics on the techniques and strategies that should be used in a classroom academic, in an orderly manner. Its objective is to strengthen the ludic strategies within the language in the boys and girls from 5 to 6 years of the Verbo Divino Educational Unit, making known the problem that could be observed within the academic classroom, the project tends to facilitate the adequate development of the behavior creating a better interpersonal relationship between the child. The use of playful strategies is very important since they are pedagogical tools to strengthen learning. In order to determine the problem, the playful strategies of the different situations that occurred with the first-grade students were applied, based on the language field. With proper education, children come into contact with different people with whom little by little they will relate, to the point that the child uses his own words to be able to express himself with a good pronunciation in the face of a discussion. The subject of my research arouses the interest of parents, for which several benefits are known that help children to have an adequate pronunciation through playful activities to stimulate language development.